2017
DOI: 10.1111/gbb.12403
|View full text |Cite
|
Sign up to set email alerts
|

BDNF genotype is associated with hippocampal volume in mild traumatic brain injury

Abstract: The negative long-term effects of mild traumatic brain injury (mTBI) have been a growing concern in recent years, with accumulating evidence suggesting that mTBI combined with additional vulnerability factors may induce neurodegenerative-type changes in the brain. However, the factors instantiating risk for neurodegenerative disease following mTBI are unknown. This study examined the link between mTBI and brain-derived neurotrophic factor (BDNF) genotype, which has previously been shown to regulate processes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…In the absence of a clear role for the inflammation response in the presentation of microcephaly, the amount of placental BDNF, a factor described as a determinant for fetal brain development, was evaluated ( 48 , 49 ). BDNF is a neurotrophic factor that is produced in placental tissue and plays an important role in cytotrophoblast differentiation and proliferation ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a clear role for the inflammation response in the presentation of microcephaly, the amount of placental BDNF, a factor described as a determinant for fetal brain development, was evaluated ( 48 , 49 ). BDNF is a neurotrophic factor that is produced in placental tissue and plays an important role in cytotrophoblast differentiation and proliferation ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a clear role for the inflammation response in the presentation of microcephaly, the amount of placental BDNF, a factor described as a determinant for fetal brain development, was evaluated (48,49). BDNF is a neurotrophic factor that is produced in placental tissue and plays an important role in cytotrophoblast differentiation and proliferation (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, evaluation of a small sample of war veterans with mTBI (n = 110) found that carriers of the minor allele of rs1157659 have less functional connectivity and atrophy in the hippocampus as compared with those that are homozygous for the WT allele (105), an association that would increase the likelihood of memory problems.…”
Section: Val66metmentioning
confidence: 99%